MENINGKATKAN KREATIVITAS SISWA MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING DI KELAS III SD - Ijirana; Irna Cahyani; Hermin (EDU RESEARCH, 2024)
This study investigated the effectiveness of Project Based Learning (PjBL) in enhancing the creativity of third-grade elementary school students while learning about rights and responsibilities as school citizens within the Civics curriculum. The research employed a Classroom Action Research (PTK) methodology, spanning two cycles. The study involved 24 third-grade students as participants. Data was collected through observation, documentation of student work, and project-based assessments. The findings revealed that the PjBL model was a successful strategy for fostering student creativity. Significant improvements were observed in student creativity throughout the project development process, the quality of the final projects, and the overall assessment scores after the implementation of the PJBL model across two cycles. This research underscores the potential of PjBL to not only deepen understanding of key concepts within the Civics curriculum, but also to cultivate essential 21st-century skills like creativity, critical thinking, and collaboration among young learners.